The Work of Nations: Preparing Ourselves for 21st-Century CapitalismThe Work of Nations: Preparing Ourselves for 21st-Century Capitalism, by ReichRobert B.. New York: Vintage Books, 1992, 339 pp., $12.00, paper. - Shrivastava, Paul; DiTomaso, Nancy (Academy of Management Review, 1994)
The article reviews the book ?The Work of Nations: Preparing Ourselves for 21st-Century Capitalism,? by Robert B. Reich.